(untitled) (Research, Society and Development, 2023)
The article aims to contribute to a better understanding of the determining factors and health conditions of the gay population in Rio Grande do Sul, highlighting their vulnerabilities and the prejudices they face. It’s worth noting that existing studies are still in their early stages, with outdated references or general approaches to the LGBT+ audience. The objective of this study is to identify the possible determining factors and health conditions of gay individuals in Rio Grande do Sul. In the context of this study, we conducted an exploratory descriptive research with a quantitative cross-sectional design, using a questionnaire as a data collection instrument through a Google electronic form. The results revealed that the majority of participants, accounting for 46.70%, are in the age range of 25 to 30 years, 99.4% identify as cisgender, and 66.23% publicly disclosed their homosexual orientation between the ages of 18 to 25. It’s relevant to note that, despite the absence of related comorbidities, a specific portion, namely 65.64% of the sample, experiences mental health issues, notably anxiety. This study holds significant importance for the gay community in the state of Rio Grande do Sul as it addresses vulnerabilities, determining factors, health conditions, and the prejudices faced by this community. By delving into these issues, this work assumes relevance as it contributes to the improvement of health services for this group and has a positive impact on the evolution of public policies aimed at this population.